Jamaliyat al-Lughah al-'Arabiyyah wa al-Wasail al-Iliktruniyah wa Isykaliyat al-Adab al-Raqmi - Muhammad, Jidda Hassan (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar, Pamekasan, 2024)
: What has been mentioned in this article represents the elements involved in creating interactive digital text, the components that are verbal and non-verbal signs. The visual and audio components that accompany every poetic or prose text. The (interactive) recipient clicks the mouse button on a specific link, connection, or options. In the form of files, icons, or links that appear on the screen, and this matter cannot be implemented on paper together, then the animated effects and the text hypertext technique, especially in the poetic sentence. We then realize how much we have missed in terms of civilization, so we accept today what we rejected yesterday and on a wide table of interpretations, explanations, and defenses. Nearly four years ago, specifically in June 2004, a creative Iraqi writer, the poet (Salman Daoud Muhammad), launched an appeal in the Iraqi newspaper (Al-Adeeb), a distinguished cultural lung with an active presence in the contemporary Iraqi cultural scene, about the electronic book and the digital realist novel. Especially regarding the novel (Muhammad Sanajla) Shadows of the One / The Vision of Digital Realism, it awakens the questions of the present with an eye to the past about how to absorb this technical newness to replace the paper novel and what is the state of the next novel, imagination and language.